المفهوم الاصطلاحي للنكاح في الفقه التراثي: دراسة نقدية فقهية - محمد، أحمد عبدالنعيم عامر (جامعة أسيوط - كلية الآداب, 2023)
شهدت العلوم عامة والإسلامية خاصة تطورا في المصطلحات على مر العصور، ومثل وجود مصطلحات قديمة في كتب التراث الإسلامي نقطة جدل عند المتحضرين المعاصرين؛ لأن علاقة الناس بالتراث ليست على نهج واحد. وقد مثل تعريف النكاح في الكتب التراثية -خاصة عند الحنفية والمالكية والشافعية- إشكالية معاصرة تقوم على وجود ألفاظ تدل على أن النكاح هو ملك البضع، أو تملك المنافع، أو اقتصار النكاح على حل الاستمتاع بالمرأة؛ بل هناك من جزم من الفقهاء بأن النكاح ينعقد بلفظ الهبة، والملك، والبيع، والإجارة، وابتعدت كثير من التعريفات عن جوهر العلاقة بين الرجل والمرأة، وعن العلة من وجود النكاح المتمثلة في إعمار الأرض، وتحقيق السكن والاستقرار لكلا الزوجين، ويهدف البحث إلى نقد تعريفات النكاح التي لا تتوافق مع مقصد التشريع من النكاح، مع بيان التعريفات الفقهية التراثية التي ارتقت بتعريف النكاح متوافقة مع مقصد الشريعة منه، ومحالة صياغة تعريف يتوافق مع حقيقة النكاح، وشرائطه، وأركانه، ومقاصده؛ لتتوافق مع النطاقات الدعوية المعاصرة. وجاء البحث في أربعة مباحث التالي: المبحث الأول- مفهوم النكاح في المذاهب الفقهية الأربعة. المبحث الثاني- قصور مفهوم النكاح الاصطلاحي في الفقه التراثي. المبحث الثالث- مفهوم النكاح في ضوء نصوص الكتاب والسنة. المبحث الرابع- المفهوم الأمثل للنكاح في ضوء مقاصد الشريعة. Sciences in general and Islamic sciences in particular have witnessed a development in terminology over the ages, and the presence of old terms in Islamic heritage books is a point of controversy for modern civilized people. Because people's relationship with heritage is not the same. The definition of marriage in the heritage books - especially among the Hanafis, Malikis, and Shafi'is - represented a contemporary problem based on the existence of expressions indicating that marriage is the property of the few, or the possession of benefits, or that marriage is limited to the solution of enjoying the woman; Rather, there are those among the jurists who are certain that marriage takes place with the terms gift, ownership, sale, and rent, and many definitions have departed from the essence of the relationship between a man and a woman, and from the reason for the existence of marriage represented in the reconstruction of the land, and the achievement of housing and stability for both spouses. The research aims to criticize the definitions of marriage that are not compatible with the purpose of the legislation of marriage, with the statement of the traditional jurisprudential definitions that elevated the definition of marriage compatible with the purpose of Sharia from it, and the impossibility of formulating a definition that is compatible with the reality of marriage, its conditions, pillars, and purposes; To comply with contemporary advocacy domains. The research came in the following four topics: The first topic - the concept of marriage in the four schools of jurisprudence. The second topic - the shortcomings of the concept of idiomatic marriage in traditional jurisprudence. The third topic - the concept of marriage in the light of the texts of the Book and the Sunnah. The fourth topic - the optimal concept of marriage in the light of the purposes of Sharia.
Keywords: الشريعة الإسلامية -- علم الأصول -- أحكام النكاح